A Review on the Application of Organoids in Food Science Research - MA Aijin, BAI Rujin, ZHOU Junjun, JIA Yingmin (Shipin Kexue, 2025)
Organoids are three-dimensional cell cultures that possess some key properties of organs, and their application in food science research has been increasingly emphasized. This paper introduces the current status of the construction and functional characterization of three major organoids, namely, intestinal, liver and brain organoids, describes recent progress in the application of intestinal, liver and brain organoids in the field of food science, discusses future prospects for the integrated application of organoids with cutting-edge technologies such as microarray technology and microfluidics, and analyzes the challenges and future directions for the application of organoid models in food science. We hope that this review can provide a reference for promoting the research and application of organoids in the field of food science.